Ethological studies of native Mexican mammals: A review - Méndez-Muñiz, Elaine Mariana; Jowers, Michael J.; Angelone, Samer; Guevara-Chumacero, Luis Manuel (THERYA, 2021)
The number of ethological studies based on Mexican mammals have increased in recent years compared to those from other Latin American countries. This study conducts an analytical review of the literature on ethological studies of native Mexican mammals. Specialized publications and electronic bibliographic databases were thoroughly searched to identify ethological studies of Mexican mammals published in scientific journals between 1900 and 2018. Information on the collection locality, state, first author nationality, country of origin of the journal, and taxa studied were recorded for each article. The articles were then classified into the 12 major ethological fields, and their data were grouped and summarized in five-year periods, and a map showing the geographic distribution of the studied localities was built using QGIS. A total of 160 studies were identified; three distinct periods could be recognized: the first (1900 to 1953) with a lack of publications, the second (1954 to1995) with low production (n = 16), and the third (1996 to 2018) with a notable increase in published articles (n = 144); in general, there was a greater participation of Mexican authors (67.5 %). Most studies (> 70 %) focused on primates, rodents, bats, and carnivores. Veracruz is the entity with the most articles, while foraging, movement, nesting, rearing, and territorial behavior were the subjects most studied, followed by social behavior, cooperation, and kinship. The greater number of studies published in the past two decades is likely the result of an increased number of mammologists and their engagement in national and international collaborative partnerships, mainly in areas such as ecology and taxonomy. Despite a relatively recent development of the field in México, an absence of studies on half of all terrestrial mammals orders, and few studies throughout northern parts of the country, mammalian ethology in México has already made significant contributions and is highly likely to continue its development and consolidation.